Incentives for Mayors to Improve Learning : Evidence from State Reforms in Ceará, Brazil - Lautharte, Ildo (World Bank, Washington, DC, 2021)
Financial incentives for students, teachers, and schools are often used to promote learning. Yet, little is known about whether similar incentives for mayors produce analogous findings. This paper investigates this question by exploring a results-based financing reform in Ceará, Brazil, which redistributes state resources to municipalities based on education performance. Comparing schools on both sides of Ceará's border over key implementation periods, the paper shows that ninth grade students who were exposed to the results-based financing performed 0.15 standard deviation higher on mathematics and language tests. These impacts increase twofold when Ceará offers technical assistance to municipalities (pedagogical and managerial) and become significant for fifth graders. These gains are seen among students in the top performance quantiles, but reformulating the results-based financing rule to penalize municipalities with more low performers significantly reduces learning gaps. The paper discuss several mechanisms: the selection of school principals, teacher training, the provision and quality of textbooks, curriculum coverage, and school homework.